El Excentrico, 1960-01-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
January 5, 1960 [5 de enero de 1960]. Ano 10, No 9. Cover has a picture of Elberta Gray at a Buddha statue. with headline "Buddha, San Francisco's beautiful Teo Gardens, the lovely lady is Elberta Gray."